设[img=180x56]17e0c2a78f1758d.png[/img],则[img=39x23]17e0a6ff4e17e32.png[/img]在[img=44x21]17e0c2a79b87ee2.png[/img]处( )。
A: 左连续
B: 右连续
C: 连续
D: 不连续
A: 左连续
B: 右连续
C: 连续
D: 不连续
C
举一反三
- 设[img=99x42]17da68fb3b5bd63.png[/img],f(x)在x=0处连续,则f'(0)=( )。 A: 2 B: 1 C: 0 D: -1
- 设[img=99x42]178697dfa09b331.png[/img],f(x)在x=0处连续,则f'(0)=( )。 A: 1 B: -1 C: 2 D: 0
- 设f(x)连续,且[img=134x53]1803d3447b5de3e.png[/img],则f(0) =( ) A: 0 B: 1 C: 2 D: -1
- 设连续型随机变量X的分布函数为[img=236x94]180387de4fc1611.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 设连续型随机变量X的分布函数为[img=236x94]1802f2bbd2ea28b.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
内容
- 0
设连续型随机变量X的分布函数为[img=236x94]18031e9684e0649.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 1
设连续型随机变量X的分布函数为[img=236x94]1802fe36702529e.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 2
设连续型随机变量X的分布函数为[img=236x94]1803a74dc4a70b4.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 3
设连续型随机变量X的分布函数为[img=236x94]1802e8d4e6f83a3.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3
- 4
设连续型随机变量X的分布函数为[img=236x94]1803395e7f08938.png[/img]则E(X) = ( ). A: 0 B: 1 C: 2 D: 3